2004
DOI: 10.1103/physrevb.69.144429
|View full text |Cite
|
Sign up to set email alerts
|

Transverse spin dynamics in a spin-polarized Fermi liquid

Abstract: The linear equations for transverse spin dynamics in a weakly polarized degenerate Fermi liquid with arbitrary relationship between temperature T and polarization γH are derived from LandauSilin phenomenological kinetic equation with general form of two-particle collision integral. The temperature and polarization dependence of the spin current relaxation time is established. It is found in particular that at finite polarization transverse spin wave damping has a finite value at T = 0.The analogy between tempe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…29 Nevertheless, there are still many questions that concern the transverse properties. To our knowledge, most of the parametrizations used to study these systems 28 are similar to that of Kohno et al and Tserkovnyak et al We thus believe that new insights can be provided by a parametrization similar to ours.…”
Section: Summary Discussion and Perspectivesmentioning
confidence: 66%
“…29 Nevertheless, there are still many questions that concern the transverse properties. To our knowledge, most of the parametrizations used to study these systems 28 are similar to that of Kohno et al and Tserkovnyak et al We thus believe that new insights can be provided by a parametrization similar to ours.…”
Section: Summary Discussion and Perspectivesmentioning
confidence: 66%
“…In contrast to the clean Fermi-liquid [11], the probability P ! ; jmj of scattering with a spin-flip does depend on jmj.…”
mentioning
confidence: 92%
“…Next, to improve convergence of the expansion of the logarithm in Eq. (9), we perform the gauge rotation of the Q matrix [14]: Q t;t 0 r Ut;rQ t;t 0 rU ÿ1 t 0 ;r; Q R K Z A ; (11) where Ut; r expfih kig expfi kg with k k i iŝ . In general, the gauge k and plasmon fields can be separated into the slow, hki and hi, and fast, k and , contributions.…”
mentioning
confidence: 99%
“…An important effort is now devoted to the exploration of the out-of-equilibrium behavior of these systems, and in particular, to the determination of their transport properties. For instance, recent experiments have probed the transport of an ultracold sample through a mesoscopic channel [2], and time of flight expansions have been used to measure the gas viscosity in the strongly correlated regime [3] where it is predicted to be close to the universal limit conjectured by string theory [4].In this Letter, we focus on spin transport properties of a Fermi gas which have now received considerable attention in the cold atom community [5-11] after previously being studied in the context of liquid 3 He [12], ferromagnetic metals [13], and spintronic materials [14]. Recent measurements of the spin-drag (SD) coefficient [15,16] have shown that the most challenging aspect of these studies is how to extract the homogeneous gas properties from measurements performed in harmonic traps.…”
mentioning
confidence: 99%
“…In this Letter, we focus on spin transport properties of a Fermi gas which have now received considerable attention in the cold atom community [5-11] after previously being studied in the context of liquid 3 He [12], ferromagnetic metals [13], and spintronic materials [14]. Recent measurements of the spin-drag (SD) coefficient [15,16] have shown that the most challenging aspect of these studies is how to extract the homogeneous gas properties from measurements performed in harmonic traps.…”
mentioning
confidence: 99%